In Silico Evaluation of Bioactive Compounds from Caesalpinia sappan L. as Lipase and Penicillin-Binding Protein Inhibitors for Antibacterial Therapy - Andi Trihadi Kusuma; Andi Sitti Fahirah Arsal (Pharmaceutical Reports, 2026)
The increasing prevalence of antibiotic-resistant bacteria has created an urgent demand for alternative antibacterial agents with distinct molecular targets. Natural compounds derived from medicinal plants continue to play an important role in early drug discovery. Caesalpinia sappan contains diverse phenolic and flavonoid constituents with potential pharmacological activity. This study investigated selected bioactive compounds from sappan wood, excluding brazilein, as potential inhibitors of bacterial lipase and penicillin-binding protein (PBP) through computational analysis. Molecular docking was employed to examine binding affinity and protein–ligand interactions, while pharmacokinetic and toxicity properties were predicted using pkCSM. The docking results revealed that sappanchalcone showed the strongest interaction with bacterial lipase, whereas protosappanin A demonstrated the highest affinity toward PBP. Both compounds formed stable interactions with important active-site residues associated with enzymatic function. In addition, ADMET prediction indicated favorable pharmacokinetic characteristics, including adequate intestinal absorption, minimal toxicity, and low potential for cytochrome P450 inhibition. Overall, the findings indicate that sappanchalcone and protosappanin A may serve as promising multi-target antibacterial candidates and provide a computational basis for future experimental validation and antibacterial drug development.